Empirical analysis of hotel strategic management accounting practices - Puspita Sari, Melinda; Adi Wibowo, Wahyu (Inovasi Analisis Data, 2025)
Purpose – This paper investigates the adoption of Strategic Innovation Management Accounting (SIMA) and related organisational and environmental variables in hospitality. This study examines how organisational lifecycle, decentralisation, perceived environmental uncertainty, IS quality and moderation between historical performance and SIMA adoption.Design/methodology/approach – A quantitative research design was used with a survey data from hotel managers to determine the influence of strategic management accounting on decision-making processes. Structural equation modeling (SEM) was utilized to examine the direct and interaction effects of organizational structure, environmental factors, and IS quality on SIMA use.Findings – The results substantiate the positive impact of perceived environmental uncertainty, decentralization, IS quality and organizational life cycle stage on SIMA adoption. Additionally, the results indicate that the influence of previous financial performance on SIMA usage are moderated by usage context, with the relationships weaker in highly uncertain environments, decentralized organizations, mature firms, and organizations with high-quality IS information. These findings game ID directors a glimpse of SIMA as a significant player in each managing financial processes and improving decisions.Originality/value – This study builds on previous research in studying which environmental and organizational conditions moderate the relationship between financial performance and SIMA usage. Different from the prior studies that emphasize on general accounting practices, this study delivers empirical evidence on the strategic adaptation of use of management accounting tools by firms in response to environmental conditions and firm design.Research Implications – The study contributes to our understanding of hotel management by highlighting the role of SIMA in sustaining performance and impact under challenging circumstances. These findings can be utilized by policymakers and industry stakeholders in formulating frameworks for facilitating the adoption of strategic accounting practices in the hospitality industry. Future studies can analyze the contextual relevance of these insights for emerging markets like Indonesia given the regulatory and technological developments.